2020
DOI: 10.1111/maps.13543
|View full text |Cite
|
Sign up to set email alerts
|

Back‐transformation mechanisms of ringwoodite and majorite in an ordinary chondrite

Abstract: We investigated the back-transformation mechanisms of ringwoodite and majorite occurring in a shock-melt vein (SMV) of the Yamato 75267 H6 ordinary chondrite during atmospheric entry heating. Ringwoodite and majorite in the shock melt near the fusion crust have back-transformed into olivine and enstatite, respectively. Ringwoodite (Fa~1 8) occurs in the SMV as a fine-grained polycrystalline assemblage. Approaching the fusion crust, fine-grained polycrystalline olivine becomes dominant instead of ringwoodite. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…It has been proposed that the combination of relatively high temperature and low pressures that characterize retrograde events leads to the back-transformation of ringwoodite into wadsleyite (Madon and Poirier 1983;Price et al 1983), or even into olivine, as for example reported for the Mbale and Y-75267 ordinary chondrites (Chen et al 1998;Kimura et al 2004;Hu and Sharp 2017;Fukimoto et al 2020). In order for reverse transformations to occur, however, the shock feature needs to be quenched at relatively slow rates, maintaining high temperatures for a few seconds (Kimura et al 2004;Ohtani et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that the combination of relatively high temperature and low pressures that characterize retrograde events leads to the back-transformation of ringwoodite into wadsleyite (Madon and Poirier 1983;Price et al 1983), or even into olivine, as for example reported for the Mbale and Y-75267 ordinary chondrites (Chen et al 1998;Kimura et al 2004;Hu and Sharp 2017;Fukimoto et al 2020). In order for reverse transformations to occur, however, the shock feature needs to be quenched at relatively slow rates, maintaining high temperatures for a few seconds (Kimura et al 2004;Ohtani et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Even if both the high‐pressure and temperature conditions required for the formation of a high‐pressure mineral are achieved, the high‐pressure mineral cannot form if the duration is not sufficiently long (e.g., Kubo et al., 2010). It is also possible that a high‐pressure mineral, which formed during the compression and equilibrium stages once, back‐transforms into its low‐pressure mineral during the subsequent adiabatic decompression stage if the cooling is slow (Fritz et al., 2017; Fukimoto et al., 2020; Hu & Sharp, 2017; Shaw & Walton, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, the pyroxene glass also forms during the back‐transformation from majorite to low‐Ca pyroxene (Fukimoto et al. 2020). Not all pyroxene glass is necessarily vitrified bridgmanite.…”
Section: Discussionmentioning
confidence: 99%
“…S4). The back-transformation from ringwoodite to olivine proceeds by an incoherent nucleation and by an interface-controlled growth mechanism; nucleation occurs on the grain boundaries of ringwoodite, and subsequently olivine grains grow (Fukimoto et al 2020). Fine-grained olivine crystal assemblages are expected to be formed in the H chondrites from wadsleyite and/or ringwoodite.…”
Section: Abundance Of High-pressure Polymorphsmentioning
confidence: 99%
See 1 more Smart Citation